2010
DOI: 10.22323/2.09030304
|View full text |Cite
|
Sign up to set email alerts
|

Is science communication its own field?

Abstract: The present comment examines to what extent science communication has attained the status of an academic discipline and a distinct research field, as opposed to the common view that science communication is merely a sub-discipline of media studies In his review How to establish PCST. Two handbooks on science communication (JCOM 7(4) December 2008), Alessandro Delfanti queries a claim in the bookCommunicating science in social contexts that science communication already 'is a distinct research field'. He sees i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…This cross-disciplinary approach (Gascoigne et al 2010) will help resolve challenging issues concerning the most effective ways of enabling science to be harnessed by society in a manner which society understands, discusses and appreciates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-disciplinary approach (Gascoigne et al 2010) will help resolve challenging issues concerning the most effective ways of enabling science to be harnessed by society in a manner which society understands, discusses and appreciates.…”
Section: Discussionmentioning
confidence: 99%
“…Five papers were commissioned by Journal of Science Communication, and broadly concluded that science communication was both interdisciplinary and multi-disciplinary, that it fell short of meeting the requirements for being a discipline, and is more properly regarded as a "field of study" (Gascoigne et al 2010, Trench and Bucchi 2010, Bell 2010, Priest 2010.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, the role of science communication in citizen science has only started to be systematically assessed. Citizen science and science communication are both relatively young and highly inter-and transdisciplinary fields of research (Gascoigne et al 2010, Jordan et al 2015) that could be more intertwined for mutual exchange and benefit. There is need for changing the reference frame that leads people's understanding from a passive knowledge transfer to active two-way knowledge exchange.…”
Section: Foster Excellent Citizen Science Communication: Promoting Trmentioning
confidence: 99%
“…Bauer and Howard, 2013;Borchelt, 2012]. However, the bibliographic characteristics of science communication research outputs have rarely been analysed in a systematic way, despite the view that such overviews of research fields are important in identifying trends and challenges [Schäfer, 2012], or for defining a discipline [Gascoigne et al, 2010].…”
mentioning
confidence: 99%